Adenocarcinoma of the sublingual salivary gland – A case report - Sahana Adirajaiah; Venkatesh Anehosur; Sumana; K. Gopalakrishnan (Journal of Oral Biology and Craniofacial Research)
Background: This report and review of literature aimed to assess a case of adenocarcinoma of sublingual salivary gland. Method: We present a case of a 52-year-old female with adenocarcinoma of sublingual salivary gland displaying painful swelling in the floor of the mouth, which was affecting her speech and mastication. Conclusion: Surgery is the treatment of choice for malignant sublingual gland tumors, but the type of surgical intervention depends on the extent of the primary tumor itself. Even though the tumors of the sublingual salivary gland are rare, they are a diagnostic challenge to every head and neck surgeon.